Successful Thrombolysis of Occluded Inferior Vena Cava Filter with IVC Syndrome - Srinivas, BC (Tabriz University of Medical Sciences, 2012)
Thrombosis of Inferior Vena Cava (IVC) following filter insertion can occur in up to 30% of the cases. The optimal management of such cases is unknown. We describe a simple and less expensive method of achieving successful recanalization of the IVC in a 40 year old hypertensive man who developed recurrent pulmonary embolism after his orthopedic treatment. An IVC filter was inserted, which developed extensive thrombosis of the whole IVC and venous system of the lower limbs. Catheter directed thrombolysis using a multiple side-hole multipurpose catheter and balloon angioplasty was carried out in order to “crush and lyse” the IVC thrombi.